Antibiograms, Resistance Genes, Class I Integrons and PFGE profiles of Zoonotic Salmonella in Malaysia - Abatcha, M.G.; Zakaria, Z.; Gurmeet, K.D.; Thong, Kwai Lin (2015)
Salmonella infections occur worldwide, in both developed and developing countries, and a major contributor to morbidity and economic costs. A total of 32 Salmonella isolates isolated from dogs (n=15/162), cats (n=1/126) and snakes (n=16/42) in the Klang valley, Peninsular Malaysia during 2012-2013, were used in this study and 6 serovars were identified. The isolates were then characterized for their susceptibility to commonly used antimicrobial agents using the standard disk diffusion method. The presence of relevant resistance genes and class 1 integrons were investigated by using PCR. Pulsed-field gel electrophoresis (PFGE) was carried out to determine the genetic diversity of these Salmonella strains. Higher resistance rates were observed for tetracycline (40.6%), nalidixic acid (21.9%), sulphamethazole-trimethoprim (18.7%), ampicillin (18.7%) followed by chloramphenicol (15.6%), streptomycin (6.25%), enrofloxacin (12.5%), cephalexin (6.25%), cephalothin (6.25%) and amoxicillin-clavulanic acid (3.12%). Nine percent (3/32) presented a single type of resistance, 6% (2/32) showed resistance to two classes of antimicrobials and 34% (11/32) were multidrugresistant (MDR) (resistant to 3 or more antimicrobials). Analysis of the carriage of resistance genes in the isolates revealed that seven (blaTEM-1, strA, strB, sulII, dfrhI, tetA, and cmlA) out of 10 resistance genes were present. Classes 1 integrons were present in 68.75% (11/16) of the resistance strains. PFGE analysis showed that the strains were very diverse and certain PFGE pattern clusters correlated well with antimicrobial resistance phenotypes. In conclusion, high rates of multidrug resistance were found among the dogs Salmonella strains.